2020
DOI: 10.1101/2020.06.04.135327
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell analysis reveals diverse stromal subsets associated with immune evasion in triple-negative breast cancer

Abstract: 44The tumour stroma regulates nearly all stages of carcinogenesis. Stromal heterogeneity in 45 human triple-negative breast cancers (TNBCs) remains poorly understood, limiting the 46 development of stromal-targeted therapies. Single cell RNA-sequencing of five TNBCs 47 revealed two cancer-associated fibroblast (CAF) and two perivascular-like (PVL) 48 subpopulations. CAFs clustered into two states, the first with features of myofibroblasts and 49 the second characterised by high expression of growth factors and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…Detailed single cell RNA-seq (scRNA-seq) data are now emerging regarding the heterogenous nature of the stromal cell population, which provides cellular resolution not previously available from bulk sequencing studies [ 37 , 38 ]. One study of human TNBC identified two distinct populations of CAFs: myofibroblastic (myCAFs) and inflammatory (iCAFs) and two populations of peri-vascular-like cells (PVL) [ 38 ]. Through analysis of large RNA-Seq datasets, the authors showed that PVL cells were associated with TILs exclusion, perhaps explaining our observation of a positive correlation between TSR and TIL.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed single cell RNA-seq (scRNA-seq) data are now emerging regarding the heterogenous nature of the stromal cell population, which provides cellular resolution not previously available from bulk sequencing studies [ 37 , 38 ]. One study of human TNBC identified two distinct populations of CAFs: myofibroblastic (myCAFs) and inflammatory (iCAFs) and two populations of peri-vascular-like cells (PVL) [ 38 ]. Through analysis of large RNA-Seq datasets, the authors showed that PVL cells were associated with TILs exclusion, perhaps explaining our observation of a positive correlation between TSR and TIL.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we assess performance of using compartment-specific proportions in downstream analyses of breast cancer outcomes and gene regulation. Using TCGA breast cancer (TCGA-BRCA) expression as a training set, we iteratively searched for compartment-specific features using TOAST + NMF ( 32 ) (Step 1 in Figure 1 ) and included canonical compartment markers for guidance using a priori knowledge ( 29 , 96 , 97 ) (see Materials and Methods). After expanding the targeted CBCS expression to these genes using a compressed sensing model based on elastic net, lasso, or ridge regression, we estimated compartment proportions.…”
Section: Resultsmentioning
confidence: 99%
“…Previous groups have emphasized reliance on a priori knowledge for deconvolving well-studied tissues, such as blood and brain ( 113 , 114 ). However, diseased tissues, like bulk cancerous tumors, especially in understudied subtypes or populations, are more difficult to deconvolve due to the similarity between compartments, many of which may be rare or reflect transient cell states ( 29 , 94 , 115 , 116 ). For this reason, we included several data-driven approaches for estimating the number of compartments from variation in the gene expression and recommended applying prior domain knowledge about the tissue of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous groups have emphasized reliance on a priori knowledge for deconvolving well-studied tissues, such as blood and brain (106,107). However, diseased tissues, like bulk cancerous tumors, especially in understudied subtypes or populations, are more difficult to deconvolve due to the similarity between compartments, many of which may be rare or reflect transient cell states (30,91,108,109). For this reason, we included several data-driven approaches in estimating the number of compartments from variation in the gene expression and recommended applying prior domain knowledge about the tissue of interest.…”
Section: Unlike Traditional Reference-based Methods That Require Compmentioning
confidence: 99%